Pendampingan Psikolinguistik Keterampilan Komunikasi Bahasa Arab Siswa dengan Metode AIR di MtsN Malinau - Diba, Farah; Nurseha, Sitti Aulia; Ilfi, Rizma; Handayani, Rika (Civiliza Publishing, 2026)
(1) Background: Foreign language skills are necessary for students to be mastered as communication skill. However, students' difficulties in mastering Arabic are caused by psycholinguistics. Psychologically, students have difficulty recording this language memory. A method is needed to involve teachers in overcoming students' difficulties. (2)Purpose of the study: The objective of this mentoring is to provide Arabic language literacy for students with a psychologically friendly method, namely the AIR method. (Auditory, Intellectualization, and Repetition); (3) Methods: Participatory Action Research is used in this method by contributing as a temporary participatory teacher at MtsNMalinau with various AIR-based programs provided.; (4) Results: It went to three cycles, the auditory implemented through chain whisper game. The intellectualization cycle applied with interactive clues to arrange sentence. The last cycle is unusual repetition of memorize, by applying vocabularies with numeric spin media tools.; (5) Conclusions: The AIR method is able to create a pleasant environment for practicing Arabic communication, by optimizing students' senses through listening, thinking, and memory without feeling psychologically forced.